2004
DOI: 10.1016/j.intcom.2003.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring reveals information requirements: the case of anaesthesia alarms

Abstract: We discuss the phenomenon of system tailoring in the context of data from an observational study of anaesthesia. We found that anaesthetists tailor their monitoring equipment so that the auditory alarms are more informative. However, the occurrence of tailoring by anaesthetists in the operating theatre was infrequent, even though the flexibility to tailor exists on many of the patient monitoring systems used in the study. We present an influence diagram to explain how alarm tailoring can increase situation awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Several studies have demonstrated that most auditory alarms are ignored, are considered to be a nuisance, or serve simply as a reminder of a previously known state of affairs (Seagull & Sanderson, 2001;Watson et al, 2004;Xiao, Mackenzie, Seagull, & Jaberi, 2000). Interface design in human factors has focused on visual displays, with only sparse research on other sensory modalities Sarter, 2000 Three experiments explored the effectiveness of continuous auditory displays, or sonifications, for conveying information about a simulated anesthetized patient's respiration.…”
Section: Information Presentation Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that most auditory alarms are ignored, are considered to be a nuisance, or serve simply as a reminder of a previously known state of affairs (Seagull & Sanderson, 2001;Watson et al, 2004;Xiao, Mackenzie, Seagull, & Jaberi, 2000). Interface design in human factors has focused on visual displays, with only sparse research on other sensory modalities Sarter, 2000 Three experiments explored the effectiveness of continuous auditory displays, or sonifications, for conveying information about a simulated anesthetized patient's respiration.…”
Section: Information Presentation Challengesmentioning
confidence: 99%
“…Although blood pressure is important for clinical monitoring, readings from an invasive arterial line would be required for a BP sonification. Most operations use noninvasive blood pressure, which is sampled only every few minutes and cannot be validly sonified (for further details see Watson et al, 2004).…”
Section: Present Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In the homecare environment this could involve customising the device to make it look discreet (O'Kane et al, 2015). In the hospital context equipment could be modified beyond the original design intent, as per accounts relating to barcoding systems (Koppel et al, 2008), alarm settings (Watson et al, 2004), physiological monitors (Cook and Woods, 1996) infusion pumps (Obradovich and Woods, 1996) and glucometers (Furniss et al, 2015).…”
Section: Equipment Replacement and Socio-technical Systems (Sts)mentioning
confidence: 99%
“…Less consideration is devoted to the detailed analysis of how practitioners themselves organize and configure their activities to avoid critical problems and alarms. There is an emerging body of studies concerned with tailoring practices and improvisational work [6,7]. However, there is a tendency in this body of literature to favour the consideration of how improvisations and workarounds can be avoided by better technical design rather than examining how those tailoring and configuring practices should be supported as an integral and necessary part of the actual work.…”
Section: ••••• Health Informatics Journal 13 (1)mentioning
confidence: 99%